Implementasi Sistem Enterprise Resource Planning (ERP) Pada Usaha Sabana Fried Chicken - Angeliana Artamevia Salsabila; Reza Damayanti; Dina Ayu Lestari; Vani Putri Aryanto; Firatna Amandari; Asqi Savira Anaya; Dian Maharani Putri (Jurnal Ilmu Sosial dan Humaniora, 2026)
The rapid development of information technology has encouraged business actors to adopt integrated systems to improve operational efficiency and competitiveness. This study aims to analyze the implementation of an Enterprise Resource Planning (ERP) system in Sabana Fried Chicken and its impact on business performance. The research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The ERP system was implemented to integrate various business functions, including inventory management, sales, procurement, finance, and operational reporting into a centralized platform. The findings indicate that ERP implementation significantly improves data accuracy, enhances coordination among business units, reduces manual recording errors, and accelerates decision-making processes. Furthermore, the system enables real-time monitoring of stock levels, sales transactions, and financial performance, thereby increasing operational efficiency and reducing unnecessary costs. The implementation also supports better business planning and control, particularly in managing multiple outlets within the franchise network. However, several challenges were identified, including high initial investment costs, employee resistance to technological changes, and the need for continuous training and technical support. Overall, the study concludes that ERP implementation provides substantial benefits for Sabana Fried Chicken by enhancing business effectiveness, operational integration, and organizational performance. Therefore, ERP can serve as a strategic digital transformation solution for fast-food franchise businesses seeking sustainable growth and improved competitiveness in the modern business environment.